The Disempowered Development of Tibet in China : a Study in the Economics of Marginalization. - Fischer, Andrew Martin, 1967- (Studies in modern Tibetan culture., 2013)
This book explores the synergy between development and conflict in the Tibetan areas of Western China from the mid-1990s onward, when rapid economic growth occurred alongside a particularly assimilationist policy approach. Based on accessible economic analysis and extensive interdisciplinary fieldwork, it represents one of the only macro-level and systemic analyses of its kind in the scholarship on Tibet, and also holds much interest for those interested in China and in development and conflict more generally.